Halalan Thayyiban fi Al-Qur’an ‘inda Wahbah Al-Zuhaily fi Tafsir Al-Munir - A Fadly Rahman Akbar; Mahmud Rifaannudin; Siti Nurhasanah (Universitas Darussalam Gontor, 2022)
With so much understanding of halal food again thayyib, researchers want to reveal a reliable narration using the Book of Tafsir Al-Munir by Wahbah Az-Zuhaili. Researchers tried to find out Halal Food again Thayyib with thematic approach, and studied through literature research, the method used is descriptive and anaisis method. As a result, halal food again thayyib is a food that is not prohibited by religion and does not harm the body. The words halal and thayyib are found in Surah Al-Maidah verse 88, which is halal food again thayyib consisting of various foods, including livestock, which are useful to the body, not destructive, not disgusting, tasty, unweding and not contrary to Allah's commandments. Eating halal food and thayyib is highly recommended by Islam because it will affect the health of the body and soul, more important things can affect a person's creed and morals, and cause the granting of a prayer and worship.